Desain Inti Reaktor SCWR (Supercritical Water Reactor) Model Teras Silinder (r, z) dengan Bahan Bakar Thorium Hasil Daur Ulang - Setiyaningsih Setiyaningsih; Yanti Yulianti; Simon Sembiring (Jurnal Teori dan Aplikasi Fisika, 2019)
The Research of the supercritical water reactor (SCWR) core design of the cylindrical core model (r, z) using the SRAC program has been done. The SRAC basic code was PIJ and CITATION. PIJ was used to calculate the fuel level and CITATION was used to calculate the reactor core level. The calculation of the reactor core has been done on the 1/4 cylinder core (r, z) and the geometry of the fuel cell was the cylindrical cell. Reactor fuel material was thorium burned 40 GWd/t and 30 GWd/t. The neutron parameters in this research were fuel enrichment, burn up, reactor core size, reactor core configurations, multiplication factor, and power density distribution. Multiplication factor (k-effective) in this research was 1.000004, which is reactor was in a critical condition. The reactor core in critical condition had the size of radius (r) was 130 cm, height (z) was 270 cm and fuel enrichment 2.8262%. The maximum power density was 130.0808 Watts /cm3 which was located at a radius of 25 cm and 135 cm high. The peak power factor in the radial direction was 1.6063 and the peak power factor in the axial direction was 1.3189.